2001
DOI: 10.1007/s002130000622
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol consumption and reward are decreased in µ-opiate receptor knockout mice

Abstract: These data fit with the reported therapeutic efficacy of MOR antagonists in the treatment of human alcoholism. Allelic variants that confer differing levels of MOR expression could provide different degrees of risk for alcoholism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
139
2

Year Published

2004
2004
2012
2012

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 199 publications
(157 citation statements)
references
References 62 publications
16
139
2
Order By: Relevance
“…Both rodent and human studies have shown that chronic cocaine and alcohol use lead to altered mu-opioid receptor expression measured as change in levels of mRNA, by quantitative autoradiography, or by PET (Unterwald et al, 1992(Unterwald et al, , 1993(Unterwald et al, , 1994Zubieta et al, 1996;Yuferov et al, 1999;Bencherif et al, 2004). In mu-opioid receptor knockout mice, opiate self-administration is blocked and both cocaine and alcohol self-administration are attenuated (Roberts et al, 2000;Hall et al, 2001). In addition, several animal models have shown that mu-opioid receptor antagonists will eliminate or curtail alcohol and psychostimulant self-administration and conditioned place preference (Altshuler et al, 1980;Myers et al, 1986;Trujillo et al, 1991;Middaugh and Bandy, 2000).…”
Section: Mu-and Kappa-opioid System and Addictionmentioning
confidence: 99%
“…Both rodent and human studies have shown that chronic cocaine and alcohol use lead to altered mu-opioid receptor expression measured as change in levels of mRNA, by quantitative autoradiography, or by PET (Unterwald et al, 1992(Unterwald et al, , 1993(Unterwald et al, , 1994Zubieta et al, 1996;Yuferov et al, 1999;Bencherif et al, 2004). In mu-opioid receptor knockout mice, opiate self-administration is blocked and both cocaine and alcohol self-administration are attenuated (Roberts et al, 2000;Hall et al, 2001). In addition, several animal models have shown that mu-opioid receptor antagonists will eliminate or curtail alcohol and psychostimulant self-administration and conditioned place preference (Altshuler et al, 1980;Myers et al, 1986;Trujillo et al, 1991;Middaugh and Bandy, 2000).…”
Section: Mu-and Kappa-opioid System and Addictionmentioning
confidence: 99%
“…Endogenous opioids acting at the -opioid receptor (MOR) serve a pivotal function in reward processing and addictive behaviors (Matthes et al, 1996;Hall et al, 2001;Olive et al, 2001;Ghozland et al, 2002;Mathon et al, 2003Mathon et al, , 2005Roth-Deri et al, 2003;Solinas et al, 2004;Jarjour et al, 2009;Mitchell et al, 2012). This is especially the case for MORs regulating the ventral tegmental area (VTA) (Bozarth and Wise, 1984;Wise, 1989;Laviolette et al, 2004), which typically suppress GABAergic inputs to VTA dopamine neurons (Johnson and North, 1992;Manzoni and Williams, 1999;Bergevin et al, 2002;Jalabert et al, 2011;Matsui and Williams, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Quantitative trait locus studies have identified the chromosomal region containing the MOR (OPRM1) gene as important to the development and perpetuation of alcohol consumption (Grisel, 2000). Also, knockout mice lacking OPRM1 do not self-administer alcohol (Hall et al, 2001;Roberts et al, 2000).…”
Section: Introductionmentioning
confidence: 99%